SET YOUR GOALS AND GET YOUR SUCCES: THE IMPACT OF ACADEMIC GOAL ORIENTATION ON ONLINE LEARNING STUDENT ENGAGEMENT - Erna Risnawati; Indah Kususma Wardhani; Valeria Yekti Kwasaning Gusti; Ayu Fahimah Diniyah Wathi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: In today's digital era, online learning has become an important breakthrough in education. Student involvement in learning plays a crucial role in successful learning achievement. This research aims to examine the role of academic goal orientation in increasing student engagement in online learning. Correlational quantitative methodology was used to analyze data from 125 students who live in the Jabodetabek area, with respondents selected using stratified random sampling, which takes into account student characteristics. The instruments used in this research were the Achievement Goal Questionnaire (AGQ) developed by Elliot & McGregor and the Student Course Engagement Questionnaire (SCEQ) developed by Handelsman. The research results show a significant positive correlation between academic goal orientation and student engagement in online learning. This research also found that female students tend to be more actively involved in online courses than male students. Another finding from this research is that both men and women have the same goal orientation for achieving academic success. Through the results of this research, it is hoped that it can contribute to the development of educational strategies that encourage gender equality in education, as well as increase awareness of the importance of academic goal orientation in increasing student engagement in online learning. Keywords: Academic achivement, online learning, higher education, goal orientation Abstrak: Dalam era digital saat ini, pembelajaran online telah menjadi terobosan penting dalam pendidikan. Keterlibatan mahasiswa dalam pembelajaran memegang peranan krusial dalam keberhasilan prestasi belajar. Penelitian ini bertujuan untuk mengkaji peran academic goal orientation dalam meningkatkan student engagement dalam pembelajaran daring. Metodologi kuantitatif korelasional digunakan untuk menganalisis data dari 125 mahasiswa yang berdomisili di wilayah Jabodetabek, dengan responden dipilih menggunakan stratified random sampling yang memperhitungkan karakteristik mahasiswa. Instrument yang digunakan dalam penelitian ini adalah Achievement Goal Questionnaire (AGQ) yang dikembangkan oleh Elliot & McGregor dan Student Course Engagement Questionnaire (SCEQ) yang dikembangkan oleh Handelsman. Hasil penelitian menunjukkan korelasi positif yang signifikan antara orientasi tujuan akademik dan keterlibatan mahasiswa dalam pembelajaran daring. Penelitian ini juga menemukan bahwa mahasiswa perempuan cenderung lebih aktif terlibat dalam kursus daring dibandingkan mahasiswa laki-laki. temuan lainnya dari penelitian ini adalah baik laki-laki maupun perempuan memiliki orientasi tujuan yang sama untuk mencapai kesuksesan akademik. Melalui hasil penelitian ini, diharapkan dapat memberikan kontribusi pada pengembangan strategi pendidikan yang mendorong kesetaraan gender dalam pendidikan, serta meningkatkan kesadaran akan pentingnya orientasi tujuan akademik dalam meningkatkan keterlibatan mahasiswa dalam pembelajaran daring. Kata kunci: academic achivement, pembelajaran daring, perguruan tinggi, tujuan belajar